(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Mishenina T. М. Dialogization of education during practical exercises and seminars of future teachers of philological specialties as a condition of the formation of didactic competence. The article reveals the essence of the concept of «learning dialogization»; dialogization justified as a didactic training for building a didactic competence of future teachers philological specialties. Lightened aspectual components didactic discourse in humanitarian training of future professionals.